An Empirical Investigation of Women Small Business Owner - Tibbits, GE.; Kandasaami, T. (Accounting Department,, 1995)
Most of the studies in the existing literature are studies done in the United State, a few in U.K. and very less from developing countries. Women are starting business at a rate nearly four times that of men in U.S. (Kaplan, 1988) and three times that of men both in Australia (ABS, 1991). and in Canada (Belcourt, 1990). Australia has got 692,700 small businesses which from 96.3% of a number of total businesses (ABS, 1990). In Australia, though women business owners are more than one third of the total small business owners, research on female entrepreneurs is still in its infancy.